Reviews about Dr. George Makdessi's remarks about Hilla and Bani Azeed - Gheder Al-Dory (آداب الرافدين, 1974)
Among the Arab tribes that played a role in the history of medieval Iraq are the Banu Asad. In particular, among them, among the more, who were able - taking advantage of the weakness of the central authorities in Iraq - to establish their own emirate in the regions of the Middle Euphrates, which lasted between 387-558 AH / 997-1162 AD. Despite their movement - as Bedouins - we can consider the Nile City, Fallujah, and Al-Jama` as being the first centers of their congregations or their groups (singularly Hilla) and in the year 495/1101 they established their capital, Hilla, as a fixed center. Long discussions have been raised about the person who built Hilla and made it the center of the emirate and when. Dr. George Makdisi dealt with this subject extensively in his article he published in 1954 in the English language, and Dr. Abdul-Jabbar Naji also addressed it in his book The More Emirate. Most of the points he came up with, meaning Dr. Makdisi.